REARING SYSTEM LOCAL BUFFALO IN LORE AND LINDU HIGHLANDS OF CENTRAL SULAWESI - Munier, F. F.; Takdir, Mohammad (Proceeding Buffalo International Conference, 2013)
Buffalo population in the highland area of Central Sulawesi declines on average 14-15% each year. This research aimed to evaluate rearing system of local buffalo in two highland regions, namely Lore and Lindu. These two regions are well known as the center for local Buffalo production in Central Sulawesi Province. Research was carried out by interviewing the buffalo breeders as respondents using questionaire prepared before hand. The results indicated that, in general, the ownership of buffalo in the Lindu highland was much higher compared to that in Lore highland in each age category. With regard to the mating system, both regions shared similar system, which was 100% natural mating. In terms of grazing system in Lore highland, Â 42.86% of buffalo was reared by fastening system and 57.14% by removable system, while Lindu it was 9.09% and 90.91%, respectively. The feed consumed buffalo which was obtained from the pasture had low nutrient content. It was concluded that the buffalo rearing system in both highland regions, Lore and Lindu, was still performed traditionally.